Protective effect of calcium dobesilate against inflammation and oxidative/nitrosative stress in the retina of a diabetic rat model - Voabil, Paula Cristina Antunes (2010)
Dissertação de mestrado em Biologia Celular e Molecular apresentada ao Departamento de Ciências da Vida da Faculdade de Ciências e Tecnologia da Universidade de Coimbra.